The Effectiveness of Quantum Teaching with Flashcard Media in Improving Reading Skills of Elementary School Students - Listy, Aldist Andhina; Erna Zumrotun (Global Action and Education for Society, 2025)
This study aims to determine the effectiveness of the quantum teaching with flashcard media in improving reading skills of elementary school students in aksara nglegena. The background of this research is the low reading ability of students in Javanese script, particularly the nglegena script. The nglegena script refers to the basic Javanese characters presented without diacritics (sandhangan) or conjunct forms (pasangan), yet it can still be read and form words or sentences. The Quantum Teaching model was implemented using the TANDUR approach (Grow, Experience, Name, Demonstrate, Repeat, and Celebrate), designed to create a fun and meaningful learning atmosphere. This research employed an experimental method with a one-group pretest-posttest design and a quantitative approach. The research subjects were 34 third-grade students at SD Negeri 1 Pekalongan. Data analysis using the Paired Sample T-Test showed a significance value (2-tailed) of 0.000, indicating a significant difference between the pretest and posttest results. Thus, the Quantum Teaching model with flashcard media proved to be effective in improving reading skills of Javanese nglegena script among third-grade students.